2016
DOI: 10.17159/sajs.2016/20150127
|View full text |Cite
|
Sign up to set email alerts
|

botanical content in the South African curriculum: A barren desert or a thriving forest?

Abstract: Botanists who are interested in education have often expressed their dismay at how plant sciences are neglected in Biology curricula, despite the important roles that plants play. While botanists in several overseas countries have studied the ways in which plant sciences are represented in curricula, no research has been done on how botany is neglected in the South African curriculum. Currently, the South African curriculum is known as the Curriculum and Assessment Policy Statements (CAPS) for Grades R–12. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…One Swiss study of several thousand participants aged between eight and 18 could on average only identify five plants, although this study also noted there was a generally poor ability to recognize species (Lindemann‐Matthies, 2002 ). Analysis of South African educational texts followed similar trends to other studies, with the authors noting the content taught is likely not sufficient to provide a strong knowledge or skills foundation in the plant sciences and is subsequently unlikely to encourage positive development of values toward plants (Abrie, 2016 ). Concerningly, recent research revealed potential threats to indigenous knowledge and observed economic development led to reductions in local ethnobotanical knowledge (Saynes‐Vásquez et al, 2016 ).…”
Section: The Known Problemmentioning
confidence: 62%
“…One Swiss study of several thousand participants aged between eight and 18 could on average only identify five plants, although this study also noted there was a generally poor ability to recognize species (Lindemann‐Matthies, 2002 ). Analysis of South African educational texts followed similar trends to other studies, with the authors noting the content taught is likely not sufficient to provide a strong knowledge or skills foundation in the plant sciences and is subsequently unlikely to encourage positive development of values toward plants (Abrie, 2016 ). Concerningly, recent research revealed potential threats to indigenous knowledge and observed economic development led to reductions in local ethnobotanical knowledge (Saynes‐Vásquez et al, 2016 ).…”
Section: The Known Problemmentioning
confidence: 62%
“…These latter two reviews could be achieved by drawing on key documents in the FOP. We suggest that this kind of coherence across the pedagogic device is critical if the logical structure of the parent discipline is to be made visible to learners (Abrie 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The textbooks in India (and things are not quite different in Brazil) are poor in pictures, and the gaps in Botany teaching become visible when students draw the plants because they draw what they see and think about them. Amélia L. Abrie (2016), author of "The botanical content in the South Africa curriculum: a barren desert or a thriving forest?" and a professor at the University of Pretoria, in South Africa, is concerned about the lack of researches regarding how Botany is neglected in the South African curriculum when compared to Zoology.…”
Section: Botany Teaching In the International Scenariomentioning
confidence: 99%
“…Thus, the way content is presented in the curriculum may not be enough to provide the necessary knowledge about the plants and consequent awareness in that area. Abrie (2016) uses other authors, such as Hershey, Honey, Uno, Wandersee and Schussler, Wilkins, who work on the theme, to claim that plants are the most important, least understood and most guaranteed of all living species. According to the author, there is a link between the neglect of plants in schools and the lack of interest of the general population for this group of living beings and, therefore, argues that the curriculum has been weakened in regard to Botany teaching.…”
Section: Botany Teaching In the International Scenariomentioning
confidence: 99%